LEGAL CERTAINTY OF TIKTOK ACCOUNTS AS DEBT GUARANTEE OBJECTS IN THE DIGITAL ECONOMY ERA - Farah Salsabilla Azura Putri; Dipo Wahyoeono Haryono (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The digital era has given rise to new intangible assets, including social media accounts such as TikTok, which now hold significant economic value through monetization, endorsements, and commercial partnerships. This phenomenon triggers a legal urgency regarding the legal status of TikTok accounts as objects of property rights and their potential as loan collateral. Utilizing a normative legal research method with various approaches—statutory, conceptual, and comparative—this study examines the position of TikTok accounts under the Indonesian Civil Code (KUH Perdata) and the mechanisms for their execution as collateral. The findings indicate that, conceptually, a TikTok account is classified as an intangible movable asset that can be legally transferred through access control. Despite its potential as collateral, the lack of explicit regulation necessitates legal updates and a reform of property law in Indonesia to accommodate these digital assets.